Effects of soil nitrogen levels on growth and defense of the native and introduced genotypes of alligator weed. (17th June 2021) - Liu, Mu; Zhou, Fang; Pan, Xiaoyun; Zhang, Zhijie; Li, Bo
Abstract: Plants growing in nutrient-rich environment are predicted to be less defended than conspecifics under nutrient limitation. However, less is known about the effects of nutrient levels on tolerance and induced resistance, and whether the effects differ between native and introduced populations of invasive plants. We performed a greenhouse experiment with introduced (the USA) and native (Argentina) genotypes of Alternanthera philoxeroides in order to study the effects of soil nitrogen levels on plant growth, constitutive and herbivore ( Agasicles hygrophila )-induced chemical defense, and herbivory tolerance. We measured total biomass, elongation rate (as proxy of growth rate), carbon and nitrogen, and the concentration of triterpenoid saponins (defensive chemicals) in leaves and roots. Constitutive resistance (+33% higher leaf triterpenoid saponins in control treatment at low nitrogen level) and tolerance [less decreased total biomass after herbivory treatment (−24% and −15% for high and low nitrogen levels)] were favored at lower nitrogen level, while induced resistance was favored at higher nitrogen level (+24% increased leaf triterpenoid saponins after herbivory treatment at high nitrogen level). Constitutive resistance and tolerance exhibited trade-offs with growth rate, while induced resistance positively correlated with growth rate. Additionally, the introduced genotypes had −6% lower content of leaf carbon in the presence of herbivores than the native genotypes at low nitrogen level, but such difference was absent at high nitrogen level. Our results indicate that soil nitrogen levels influence the preference of different defensive strategies of plant, and interweave with herbivory to determine the performance of introduced genotypes.